A Game

George plays a game with two 6-sided fair dice:

  • Rolling a total of 2 on any turn results in a loss (and the game ends).

  • On the first turn, rolling a total of 12 results in a win (and the game ends).

  • On the first turn, if a total other than 2 and 12 is rolled, then this becomes the target total.

  • In the following turns, the target total must be rolled again for a win (and the game to end). However, if a total of 2 is rolled first, then this still results in a loss (and the game ends).

The probability that George wins can be expressed as a fraction a b \dfrac{a}{b} , where a a and b b are coprime positive integers.

What is the value of a + b a+b ?


The answer is 4483.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Judy Gu
Apr 28, 2017

(1) Let n = the total of the roll of the 2 dices. P(n) = 1 36 \frac{1}{36} , 2 36 \frac{2}{36} , 3 36 \frac{3}{36} , 4 36 \frac{4}{36} , 5 36 \frac{5}{36} , 6 36 \frac{6}{36} , 5 36 \frac{5}{36} , 4 36 \frac{4}{36} , 3 36 \frac{3}{36} , 2 36 \frac{2}{36} and 1 36 \frac{1}{36} for n = 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 and 12 respectively.

(2) P(George wins) = P(n=12 in the 1st turn) + P(n=target total in a subsequent turn | 3<=n<=11 in the 1st turn) , and P(n=12 in the 1st turn) = 1 36 \frac{1}{36}

(3) To determine P(George wins | 3<=n<=11 in the 1st turn), note the probability that n is NOT equal to the target total in any subsequent turn = 1-P(n)- 1 36 \frac{1}{36} , since we need to remove the probability that n = 2. The equation for calculating P(George wins) for each n(3<=n<=11) actually turns out to be a geometric series :

(4) P(George wins | n=3 in the 1st turn) = 2 36 \frac{2}{36} * 2 36 \frac{2}{36} + 2 36 \frac{2}{36} * 36 2 1 36 \frac{36-2-1}{36} * 2 36 \frac{2}{36} + 2 36 \frac{2}{36} * 36 2 1 36 \frac{36-2-1}{36} * 36 2 1 36 \frac{36-2-1}{36} * 2 36 \frac{2}{36} ........., = 1 324 \frac{1}{324} * 12 = 1 27 \frac{1}{27}

(5) Similarly, P(George wins | n=4 in the 1st turn) = 3 36 \frac{3}{36} * 3 36 \frac{3}{36} + 3 36 \frac{3}{36} * 36 3 1 36 \frac{36-3-1}{36} * 3 36 \frac{3}{36} + 3 36 \frac{3}{36} * 36 3 1 36 \frac{36-3-1}{36} * 36 3 1 36 \frac{36-3-1}{36} * 3 36 \frac{3}{36} ........., = 1 16 \frac{1}{16}

(6) P(George wins | n=5 in the 1st turn) = 4 36 \frac{4}{36} * 4 36 \frac{4}{36} + 4 36 \frac{4}{36} * 36 4 1 36 \frac{36-4-1}{36} * 4 36 \frac{4}{36} + 4 36 \frac{4}{36} * 36 4 1 36 \frac{36-4-1}{36} * 36 4 1 36 \frac{36-4-1}{36} * 4 36 \frac{4}{36} ........., = 4 45 \frac{4}{45}

(7) P(George wins | n=6 in the 1st turn) = 5 36 \frac{5}{36} * 5 36 \frac{5}{36} + 5 36 \frac{5}{36} * 36 5 1 36 \frac{36-5-1}{36} * 5 36 \frac{5}{36} + 5 36 \frac{5}{36} * 36 5 1 36 \frac{36-5-1}{36} * 36 5 1 36 \frac{36-5-1}{36} * 5 36 \frac{5}{36} ........., = 25 216 \frac{25}{216}

(8) P(George wins | n=7 in the 1st turn) = 6 36 \frac{6}{36} * 6 36 \frac{6}{36} + 6 36 \frac{6}{36} * 36 6 1 36 \frac{36-6-1}{36} * 6 36 \frac{6}{36} + 6 36 \frac{6}{36} * 36 6 1 36 \frac{36-6-1}{36} * 36 6 1 36 \frac{36-6-1}{36} * 6 36 \frac{6}{36} ........., = 1 7 \frac{1}{7}

(9) P(George wins | n=8 in the 1st turn) = 5 36 \frac{5}{36} * 5 36 \frac{5}{36} + 5 36 \frac{5}{36} * 36 5 1 36 \frac{36-5-1}{36} * 5 36 \frac{5}{36} + 5 36 \frac{5}{36} * 36 5 1 36 \frac{36-5-1}{36} * 36 5 1 36 \frac{36-5-1}{36} * 5 36 \frac{5}{36} ........., = 25 216 \frac{25}{216}

(10) P(George wins | n=9 in the 1st turn) = 4 36 \frac{4}{36} * 4 36 \frac{4}{36} + 4 36 \frac{4}{36} * 36 4 1 36 \frac{36-4-1}{36} * 4 36 \frac{4}{36} + 4 36 \frac{4}{36} * 36 4 1 36 \frac{36-4-1}{36} * 36 4 1 36 \frac{36-4-1}{36} * 4 36 \frac{4}{36} ........., = 4 45 \frac{4}{45}

(11) P(George wins | n=10 in the 1st turn) = 3 36 \frac{3}{36} * 3 36 \frac{3}{36} + 3 36 \frac{3}{36} * 36 3 1 36 \frac{36-3-1}{36} * 3 36 \frac{3}{36} + 3 36 \frac{3}{36} * 36 3 1 36 \frac{36-3-1}{36} * 36 3 1 36 \frac{36-3-1}{36} * 3 36 \frac{3}{36} ........., = 1 16 \frac{1}{16}

(12) P(George wins | n=11 in the 1st turn) = 2 36 \frac{2}{36} * 2 36 \frac{2}{36} + 2 36 \frac{2}{36} * 36 2 1 36 \frac{36-2-1}{36} * 2 36 \frac{2}{36} + 2 36 \frac{2}{36} * 36 2 1 36 \frac{36-2-1}{36} * 36 2 1 36 \frac{36-2-1}{36} * 2 36 \frac{2}{36} ........., = 1 27 \frac{1}{27}

(13) Now, add (4) through (12) and 1 36 \frac{1}{36} , we get 2 27 \frac{2}{27} + 2 16 \frac{2}{16} + 8 45 \frac{8}{45} + 50 216 \frac{50}{216} + 1 7 \frac{1}{7} + 1 36 \frac{1}{36} = 1963 2520 \frac{1963}{2520}

(14), Since the two numbers 1963 and 2520 are co-primes, the final answer is 1963 + 2520 = 4483 \boxed{4483}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...